Pertanggungjawaban Pemerintah Dalam Mengeluarkan Keputusan Yang Menimbulkan Kerugian - Suhardi, Muhammad (Universitas Teknologi Mataram, 2023)
Abstract - This article is intended to study and examine how the government is accountable for issuing decisions that cause harm. This is prescriptive normative research, namely looking for arguments based on research results in providing an assessment of what is right and wrong according to the law. Using the concept of government accountability within the framework of a rule of law with the principle of legality as the knife of analysis. The result is that the government's accountability for decisions that cause losses has not met expectations due to various constraints and obstacles. Keywords: Government; Decision; Loss; Accountability